THE ROLE OF GAME METHODS IN TEACHING A FOREIGN LANGUAGE TO PRESCHOOL CHILDREN: A COMPREHENSIVE THEORETICAL AND PRACTICAL ANALYSIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article presents a comprehensive examination of the theoretical foundations and practical applications of utilizing game-based methodologies in teaching foreign languages to preschool-aged children, with a particular focus on the German language. The analysis delves into the intricate relationship between early childhood developmental psychology and language acquisition processes, investigating how structured play activities can effectively stimulate cognitive, linguistic, and socioemotional development. The research explores the multifaceted role of play within educational contexts, detailing specific mechanisms through which game-based learning fosters interest, enhances auditory and visual perception, and creates optimal conditions for natural language assimilation. Drawing upon empirical observations, contemporary pedagogical innovations, and cross-cultural educational practices, this work provides an extensive framework of methodological recommendations for educators. The article aims to establish game methods not merely as supplementary activities but as central, indispensable components of a developmentally appropriate preschool foreign language curriculum, ultimately contributing to the formation of positive, lasting attitudes toward language learning during these formative years.